Kintsugi Philosophy for Auditors - Valeria Trifena Tulangow (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study explores the understanding of audit accounting by looking at the audit process through the art of Kintsugi. This research is empirical research using the interpretivism paradigm and collecting data using the interview method on several auditors and clients who are friends of the researcher and performing document analysis. Negotiation has several key behaviours, including communication, data, and service. The interests of auditors and clients are a part that is united by communication, data, and service. Negotiations between auditors and clients create the impression that gold flows through every existing crack. While auditing brings convenience, it never reaches perfection. The audit process can be seen as a kintsugi process which ultimately produces something more valuable through a purification process. This research complements the understanding of previous research. Namely, the performance of auditors can purify financial statements and even broader organizational settings.